1998
DOI: 10.1046/j.1365-294x.1998.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for different migration routes of freshwater fish into Norway revealed by analysis of current perch (Perca fluviatilis) populations in Scandinavia

Abstract: To elucidate the colonization of freshwater fish into Norway following the last deglaciation of Europe 10,000 years ago, we have performed a survey using mitochondrial DNA variation (20 populations) and multilocus DNA fingerprinting (14 populations) of the widely distributed perch (Perca fluviatilis) from the Scandinavian peninsula and the Baltic Sea. Sequence analysis of a 378 bp segment of the perch mitochondrial control region (D-loop) revealed 12 different haplotypes. A nested clade analysis was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 31 publications
2
52
0
Order By: Relevance
“…Overall mtDNA genetic diversity of yellow perch is lower than that of walleye Sander vitreus , and roughly equivalent to that determined for Eurasian perch Perca fluviatilis (Refseth et al, 1998;Nesbo et al, , 1999. Similarly, P. fluviatilis had relatively low allozymic genetic diversity (Gyllensten et al, 1985;Bodaly et al, 1989).…”
Section: Genetic Diversity Of Yellow Perch Populationssupporting
confidence: 48%
“…Overall mtDNA genetic diversity of yellow perch is lower than that of walleye Sander vitreus , and roughly equivalent to that determined for Eurasian perch Perca fluviatilis (Refseth et al, 1998;Nesbo et al, , 1999. Similarly, P. fluviatilis had relatively low allozymic genetic diversity (Gyllensten et al, 1985;Bodaly et al, 1989).…”
Section: Genetic Diversity Of Yellow Perch Populationssupporting
confidence: 48%
“…Thus, species composition in LG1 is random but spatially autocorrelated due to dispersal limitation of species (see Tuomisto & Ruokolainen, 2006 and references therein). Although lakes in LG1 are characterized by widespread species, differences in the mode of dispersal, e.g., active versus passive (see Kappes & Haase, 2012), in combination with different post-glacial recolonization routes (e.g., Refseth et al, 1998;Tollefsrud et al, 2008), time from deglaciation (see Andrén et al, 2011) and the presence of geographical barriers may explain our findings. The partial Mantel tests showed that environmental distances are more important than geographical distances in LG2.…”
Section: Species Richnessmentioning
confidence: 75%
“…However, the precise location of this refugium for northern pike is uncertain [19,25]. Notably, Scandinavia has probably been colonization from the central European refugium as well as from an eastern refugium by the circumpolar haplogroup, as also implied for the Eurasian perch (Perca fluviatilis) recolonization of Scandinavia [31,36]. Thus, northern Europe has most likely been recolonized from at least two different northern pike refugia and not one as earlier suggested [16,24].…”
Section: Geographic Origins Of the Northern Pike Mtdna Lineagesmentioning
confidence: 85%